Architectural surfaces : details for architects, designers and artists - Juracek, Judy A. (London : Thames & Hudson, 2005)
Foreword by Peter Pennoyer; 1. Walls; 2. Facades; 3. Ornaments & Mouldings; 4. Columns, Posts & Arches; 5. Windows; 6. Doorways; 7. Ceilings & Roofs; 8. Floors & Pavement; Glossary, bibliography and Sources; 2 Free CD-ROMs.
Includes bibliography and bibliographical references.
boek